Efektivitas Reward Organisasi Dalam Meningkatkan Komitmen Guru di SMA Plus Sedayu Nusantara Medan - Harianti Wira Pratama (UMSU, 2023)
The main objective of this study is to test the effectiveness of the reward system that has been established in increasing teacher work commitment in learning activities at SMA Plus Sedayu Nusantara Medan. This research is a type of mixed methods research. The population in the study were foundations, school principals and subject teachers and as many as 45 respondents were taken from a portion of the population. Methods of data collection with interviews and questionnaires. Methods of data analysis using descriptive methods and descriptive statistical analysis using person product moment correlation. The results of this study indicate that the reward system that has been established at Sedayu Nusantara Medan Plus High School is quite well received by teachers, then work commitment at Sedayu Nusantara Medan Plus High School is already good as seen from the willingness of teachers to continue to innovate in maximizing the learning process, and rewards have a positive influence significant to the work commitment of Sedayu Nusantara Medan Plus High School teachers where it can be seen from the rxy value or the influence value of the x variable on the y variable which is the teacher's commitment whose results show a value of 0.562 and if this value is consulted with the r moment value table, the remaining 0.438 is influenced by the factor - another factor.